Evaluation of oxides of nitrogen emissions for the purpose of their transient regulation from a direct injection diesel engine. (1st January 2001) - Yacoub, Yasser; Atkinson, Chris
The concept of defining a regulatory standard for the maximum allowable emissions of oxides of nitrogen (NOx ) from a heavy-duty diesel engine on an instantaneous basis is presented. The significance of this concept from a regulatory point of view is the possibility to realise a steady brake specific NOx emissions result independent of the test schedule used. The emissions of oxides of nitrogen from a state-of-the-art direct injection diesel engine have been examined on an integral as well as on an instantaneous basis over the Federal Test Procedure as well as over several other arbitrary transient cycles generated for this study. Three candidate standards of specific NOx emissions have been evaluated on a real-time, continuous basis. These include brake power specific, fuel mass specific, and carbon dioxide mass specific NOx emissions. Retaining the stock engine control module, the carbon dioxide specific emissions of NOx have been shown to be the most uniform, varying only by about 30% of its mean value regardless of the test schedule or engine operation. The instantaneous fuel specific NOx emissions are shown to be relatively less invariant and the least steady are the brake power specific emissions with a coefficient of variation of up to 200%. Advancing injection timing has been shown to have a wide range of authority over the specific emissions of oxides of nitrogen regardless of the units used, when operating at full load in the vicinity of peak torque speeds. The carbon dioxide specific NOx emissions have shown a linear dependence on the power specific emissions, independent of the examined operating conditions. The trade-off between better brake thermal efficiency, lower exhaust gas temperature at advanced timing and lower NOx emissions has also been shown to be independent of the units of the specific standard used.